Reduction of Glycolysis Intermediate Concentrations in the Cerebrospinal Fluid of Alzheimer’s Disease Patients - Bergau, Nick; Maul, Stephan; Rujescu, Dan; Simm, Andreas; Navarrete Santos, Alexander (Frontiers in Neuroscience, 2019)
The profile of 122 metabolites in the cerebrospinal fluid (CSF) of patients suffering from Alzheimer’s disease (AD) and controls was studied. Among the 122 metabolites analyzed, 62 could be detected. Statistically significant differences between the AD and control group were only detected for metabolites of the glycolysis. Thus, accurate quantification of 11 glycolytic metabolites was done. At this, we detected a significant reduction of five of them, namely phosphoenolpyruvate, 2-phosphoglycerate, 3-phosphoglycerate, pyruvate and dihydroxyacetone phosphate in the AD CSF compared to controls. These results correlate with the known reduction of glucose metabolism in the brain of patients with AD and indicate that metabolic analysis of the central carbon metabolism can be a potential tool in AD diagnostic. Although the ROC analyses of the metabolites do not reach the level of the diagnostic quality of AD biomarkers, the combination of glycolysis metabolites with the established biomarkers led to an improvement in sensitivity and specificity. Thus, metabolic markers could increase diagnostic safety and represent an approach to characterize the progression of the disease.